Penerapan Model Pembelajaran Upanisad Berbasis Tematik Untuk Meningkatkan Aktivitas dan Prestasi Belajar Siswa Kelas III di SD Negeri 2 Busungbiu - Agustina, Kadek Wahyu; Suwendra, I Wayan (Jurnal Widya Sastra Pendidikan Agama Hindu, 2023)
The problem studied in this study was the low activity and learning achievement for third grade students at SD Negeri 2 Busungbiu. The purpose of this study was to examine the application of the Thematic basid Upanisad Learning Models to increase the activity and achievement of third grade students at SD Negeri 2 Busungbiu in the 2022/2023 academic year. In order to achieve the above objectives, several theories were used, including: Upanisad Learning Models, and relevant research results. The research was designed using the Classroom Action Research method with 11 research subjects consisting of 6 male students and 5 female students at SD Negeri 2 Busungbiu. The research procedure uses a cycle system consisting of 2 cycles, where each cycle consists of 4 stages, namely: planning, implementation of action, observation evaluation analysis, and reflection. Data collection methods used tests for learning achievement data, and observations for student activity data. Data analysis used descriptive quantitative and qualitative methods. The research results can be explained as follows. In the implementation of cycle I, the average student activity towards learning was 51,51% and the average class achievement (M) was 68,18, classical absorption (DS) 68,18% and classical learning mastery (KB) 63% category low. Then the implementation of cycle II averaged activity on learning by 85,96% and class average learning achievement was 85,45, classical absorption (DS) 85,45%, and classical learning mastery (KB) 100% verry high category. The results of the study were recommended to teachers, to apply the Tematic basid Upanisad Learning Model appropriately and correctly in an effort to increase student activity and achievement